2022
DOI: 10.4308/hjb.29.3.288-300
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Phylogenetic Analysis of Fungi Contaminants Associated with In Vitro Cultured Banana Based on ITS Region Sequence

Abstract: This study characterized, identified and conducted phylogenetic analysis on fungi contaminants in vitro bananas based on the sequence of inter-space (ITS) regions. Genomic DNA was extracted from the pure culture of fungi contaminants, amplified and sequenced using ITS1 and ITS4 markers. Analysis of the sequences using MEGA 7 Software at higher similarity sequence identified five Aspergillus spp., three Penicillium spp., one each of Fusarium, Trichoderma and Cladosporium as the contaminants. The genetic distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Tissue culture technology is useful for providing disease-free and consistent planting materials that can be made available throughout the year [45]. Thus, the technique is crucial for banana and plantain micropropagation, ensuring the availability of genetically identical and disease-free plantlets for commercial production of the crop, which would significantly improve food security and economic benefits for farmers and consumers around the world [10]. Despite the multiple benefits of tissue culture technologies to banana and plantain production and agricultural growth, contamination has been a serious impediment to their use in crop micropropagation [46].…”
Section: Microbial Contamination In Musa Spp Tissue Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Tissue culture technology is useful for providing disease-free and consistent planting materials that can be made available throughout the year [45]. Thus, the technique is crucial for banana and plantain micropropagation, ensuring the availability of genetically identical and disease-free plantlets for commercial production of the crop, which would significantly improve food security and economic benefits for farmers and consumers around the world [10]. Despite the multiple benefits of tissue culture technologies to banana and plantain production and agricultural growth, contamination has been a serious impediment to their use in crop micropropagation [46].…”
Section: Microbial Contamination In Musa Spp Tissue Culturementioning
confidence: 99%
“…Accurate identification of common contaminants is required to effectively combat the threat of fungal contamination. Animasaun et al [10] isolated and identified eleven fungi strains of five genera, Aspergillus, Cladosporium, Fusarium, Penicillium, and Trichoderma as the significant contaminants of in vitro banana culture. In early studies, Odutayo et al [60] and Rahman et al [61] identified four and five genera of fungi contaminants in tissue culture materials, respectively.…”
Section: Fungal Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, fungal contaminants that often contribute to contamination include Aspergillus flavus , A. niger , Fusarium spp., and Trichoderma spp. ( Agbadje et al, 2021 , Animasaun et al, 2022 , Kithaku et al, 2019 , Mokbel et al, 2017 ). Inadequate treatment of explant contamination can result in less regeneration capacity, decreased callus formation, and suppressed adventitious shoot growth ( Cobrado and Fernandez, 2016 , El-Banna et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%